Correlation Analysis on the SGS Velocity between Phases in an Isotropic Gasparticle Two-phase Flow with FDF Model - Hanhui Jin Yuhui Chen Jianren Fan Kun Luo (热科学学报：英文版, 2012)
Correlation of the SGS （sub-grid scale） velocity between the two phases in an isotropic gas-particle two-phase flow was numerically investigated with FDF model. The results show the SGS gas velocity seen by the particles varies with the relative velocities between particle phase and gas phase. The relative velocity between the two phases produces the effect of the anisotropic turbulence on the particles. The variation of Stokes number influ- ences the magnitude of the interaction between the two phases.